1998
DOI: 10.1095/biolreprod58.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Messenger Ribonucleic Acid Encoding Monocyte Chemoattractant Protein-1 is Expressed by the Ovine Corpus Luteum in Response to Prostaglandin F2α 1

Abstract: To investigate expression of monocyte chemoattractant protein-1 (MCP-1) in the ovine corpus luteum, a partial cDNA was produced by reverse transcription-polymerase chain reaction. This cDNA was 89% identical to that reported for bovine MCP-1 mRNA. In experiment 1, steady-state concentrations of mRNA encoding MCP-1 were measured in pools of luteal tissue collected on Days 3, 6, 9, 12, and 15 of the estrous cycle (estrus = O; n = 4/day). There were no differences in mRNA concentrations for MCP-1 among any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 0 publications
1
28
2
Order By: Relevance
“…In the present study, we have shown that cells expressing MCP-1 mRNA are steroidogenic luteal cells in normally cycling rats. This conclusion appears to conflict with the results reported by Haworth et al [9], who found that large steroidogenic cells, as assessed immunohistochemically with an antibody recognizing tissue inhibitor of metalloproteinase-1, did not contain MCP-1 mRNA in corpora lutea of prostaglandin F 2␣ -administered sheep. The reasons for this discrepancy are not certain at present, but they could include 1) the fact that small luteal cells in the sheep express MCP-1, 2) a difference in the conditions of the animals (normal rats vs. prostaglandin F 2␣ -treated sheep), or 3) a difference in the antibodies used to identify steroidogenic cells.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In the present study, we have shown that cells expressing MCP-1 mRNA are steroidogenic luteal cells in normally cycling rats. This conclusion appears to conflict with the results reported by Haworth et al [9], who found that large steroidogenic cells, as assessed immunohistochemically with an antibody recognizing tissue inhibitor of metalloproteinase-1, did not contain MCP-1 mRNA in corpora lutea of prostaglandin F 2␣ -administered sheep. The reasons for this discrepancy are not certain at present, but they could include 1) the fact that small luteal cells in the sheep express MCP-1, 2) a difference in the conditions of the animals (normal rats vs. prostaglandin F 2␣ -treated sheep), or 3) a difference in the antibodies used to identify steroidogenic cells.…”
Section: Discussioncontrasting
confidence: 73%
“…The presence of MCP-1 mRNA or protein in the corpus luteum has been reported for various animal species, including murine [7,12,13], bovine [8,10,14], ovine [8,9], and human [11], but the identity of the cell type(s) responsible for the Mcp-1 gene expression has been ambiguous. In the present study, we have shown that cells expressing MCP-1 mRNA are steroidogenic luteal cells in normally cycling rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entrance of macrophages is probably dependent on the release of chemotactic factors TC # 360 from the CL. Previous authors have shown that regressing CL in the rat [10] and sheep [30] express monocyte chemoattractant protein 1 (MCP-1) and that PRL induces the expression of this protein in the CL of the rat [11]. In the present study, macrophage accumulation was not affected by any treatment except CB154, which specifically inhibits PRL secretion.…”
Section: Discussioncontrasting
confidence: 46%
“…MCP-1 is also normally expressed in the corpus luteum (Tsai et al, 1997) and partially involved in structural and functional luteolysis in humans (Arici et al, 1997), ruminants (Tsai et al, 1997;Townson et al, 2002) and rodents (Bowen et al, 1999). The majority of cells expressing MCP-1 in the corpus luteum are inflammatory cells, including macrophages, which may play a partial role in regression of the corpus luteum since MCP-1 expression in the corpus luteum increases in response to PGF 2α (Haworth et al, 1998). MCP-1 not only serves as a specific chemo-attractant for monocytes but also stimulates the proliferation of vascular smooth-muscle cells and production of cytokines from monocytes and macrophages (Vaddi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%